Utilizing of flower pollination algorithm for brushless DC motor speed controller - Motakabber, S. M. A.; Zahirul Alam, A. H. M.; Nordin, Anis Nurashikin; Mahmud, Md (2020)
Currently, brushless direct current (BLDC) motors are becoming popular in electric vehicles, automation systems and industrial applications. Basically, the BLDC motors are a special type of electronically controlled electric motor systems. In fact, the successful advancement of electronic technology has made these motors a reality. Without an electronic controller, it is impracticable to run this motor. Thus, it is easily conceivable that the motor controller plays an important role in the overall performance of BLDC motors. Many types of controllers have already been developed for these motors. However, poor efficiency, complexity, bulky size, slow response time, etc. are still challenging tasks to solve these problems. Various algorithms are proposed for designing the controller. Proportional Integral Derivative (PID) controller is the most common control system for the BLDC motor. If the PID controller is modified with a new algorithm, better results can be obtained from the BLDC motor. In this study, a Flower Pollination Algorithm (FPA) has been proposed for the controller to control the speed of BLDC motor. The best outcome of this research is stable is speed and reduce rising time. This study was done by using MATLAB/ Simulink software. The results show a new direction in the improvement of the controller design.